Investigating the effect of insulin on myometrial contractility. (16th November 2010) - Heath, AM; Alquahtni, S; Dawood, F; Quenby, S; Wray, S
Abstract : Diabetes in pregnancy accounts for a disproportionately high rate of Caesarean sections (CS). Insulin is widely prescribed to attain normoglycaemia in diabetic pregnancies. The authors analysed the effect of insulin on spontaneous and oxytocin-induced myometrial contractility. Methods: Contractility and simultaneous intracellular Ca signals in response to increasing concentrations of insulin (7 pM to 700 nM) were recorded from both human and late pregnant rat myometrial strips. These were dissected from biopsies obtained with full consent from women undergoing term elective CS and rats humanely killed at late gestation (22 days). Ouabain (Na pump inhibitor) or tetraethylammonium (K channel inhibitor) was added to contracting myometrium combined with insulin to examine the mechanism of insulins action. Results: A dose dependent decrease in contractility in response to insulin was observed in human (n=11) and rat myometrium (n=5) which was significant at concentrations ≥7 nM relative to control period. The decrease in force was mirrored in the underlying Ca transients. Insulin caused a significant greater decrease in myometrial contractility in non-diabetics (n=11) compared to diabetics (n=8). Both 10 μM ouabain and 5 mM tetraethylammonium (TEA) with insulin inhibited the negative effect of insulin on contractility. Conclusion: Insulin causes a dose-dependent decrease in amplitude of spontaneous and oxytocin stimulated contractions in human and rat myometrium. The decrease in calcium transients suggests that insulin is acting by decreasing calcium currents, and may partially stimulate the Na pump resulting in cell hyperpolarisation The inhibitory effect of TEA on myometrial responses to insulin suggests insulin may also impede conductance of K + .